Evaluation of Learning Outcomes of Moral Faith Subjects during Covid-19 Pandemic at MIN East Kotawaringin - Said, Amad; Muslimah, Muslimah (Bulletin of Science Education, 2021)
This article explores data on the assessment of the learning outcomes of Akidah Akhlak during the covid-19 pandemic starting from the stages of preparation, implementation and reporting of the learning results of Akidah Akhlak at Madarasah Ibtidayah Negeri (MIN) 1 Kotawaringin Timur. This research uses qualitative type, namely the author discussed in detail using logical analysis and using the theory derived from the book and the results of research on planning and implementation of the evaluation. Data collection techniques through live interviews so that the author obtains information directly from the subjects studied related to the assessment of the learning results of lesson Akidah Akhlak at Madarasah Ibtidayah Negeri (MIN) 1 Kotawaringin. The results showed that Preparation of evaluation or assessment of the learning results are very good because before conducting evaluation activities in advance by looking at existing competency standards, as well as basic competencies, indicators, subject matter and also in advance by determining the purpose of evaluation to know the extent of the teacher's success in delivering learning or materials to students. In addition, there is also an identification of learners that aims to understand the learners in order to follow up the results of learners during the learning process and create a question grid before the creation of the question is made. The second Implementation of assessment of the results of Aikdah Akhlak at Madarasah Ibtidayah Negeri (MIN) 1 Kotawaringin, has not been fully done because it only uses several kinds of tests that use written tests in the form of multiple choice, essays, oral, and oral test evaluation forms that are direct question and answer, while for practical tests sometimes only a few classes that carry out practical tests. Keyword: Learning Outcome, Learning Evaluation, Learning at Pandemic Time